Sharpening the other side of the dual edged systematic review sword: Expecting more from our users - Conference presentation - Sikora, Lindsey; Bass, Michelle B (Université d'Ottawa | University of Ottawa, 2018)
Introduction: Librarians are often well prepared before meeting with researchers to discuss their knowledge syntheses needs, specifically systematic reviews (SRs). However, what are the expectations we place on our users to come prepared? Methods: We completed an environmental scan of select medical library websites in the United States, Canada, the United Kingdom, and Australia, examining academic, government and hospital libraries. We searched for information about systematic reviews including guides, services, forms and documents that were required to be filled by users before meeting with a librarian. Results: Preliminary results indicated that there are few institutions that have clearly delineated their expectations of the user before meeting with a librarian for planning a systematic review. Libraries that had more comprehensive systematic review information available to users were more likely to require users to complete a form prior to meeting with a librarian. Most Canadian academic libraries had a consultation form requirement. Australian academic libraries had more interdisciplinary guides on systematic reviews. Discussion: A similar level of preparedness expected from librarians when planning a systematic review should also be extended to users. By delineating what is expected from users ahead of time, both members can properly plan. We have created a set of best practices for SR services, bringing together all relevant information found on forms, documents, and websites from our scan, in the hope of providing the health librarianship community with guidelines they can adapt and implement within their institution or organization.
Keywords: systematic reviews; knowledge synthesis; library services